Energy and cost optimization in the life cycle of nearly zero energy buildings using parametric calculations. (August 2019) - Venus, D; Weiss, T; Moser, C; Hatt, T; Ploß, M; Roßkopf, T
Abstract: Possible cost saving potentials in the planning and construction of future building standards are often not sufficiently assessed, as only a few possible variants are considered in the traditional planning process. Often planning and analysis are not carried out in parallel, and the various possibilities are discarded at an early stage. If, on the other hand, several variants are realistically compared in the planning phase, including life-cycle costs, a profound decision can be made. Therefore parameter studies were carried out as part of the national research project "KoPro LZK+" (cost and process optimization in the life cycle of nearly zero energy buildings) for seven buildings, five multi-family buildings, a school and an office building. For this purpose, a VBA macro was programmed in MS-Excel©, which automatically carries out energy demand calculations in the "Passive House Planning Package" (PHPP) and life-cycle cost calculations in the tool "econ calc". A total of more than 216, 000 variants were investigated in this way, whereby on the one hand a variety of technologies, such as insulation of the building envelope, ventilation or electricity and heat supply, and on the other hand a variation of the boundary conditions (such as observation period, user behaviour, energy price increases or CO2 costs) were carried out. The results were analysed energetically and economically over the life cycle (separately from each other and combined) with the objectives of identifying coherences, deriving trends and optimizations over the life cycle.